Budding and tumor—infiltrating lymphocytes — combination of both parameters predicts survival in colorectal cancer and leads to new prognostic subgroups - Lang-Schwarz, Corinna; Melcher, Balint; Haumaier, Franziska; Lang-Schwarz, Klaus; Rupprecht, Thomas; Vieth, Michael; Sterlacci, William (Human Pathology, 2018)
Tumor budding is an independent prognostic factor in colorectal cancer (CRC) and has recently been well defined by the International Concensus Conference on Tumor Budding (ITBCC). Tumor—infiltrating lymphocytes (TILs) are also an issue in different human cancers and correlate with prognosis in CRC. Here we evaluate the combination of budding and TILs in CRC with regard to prognosis. Hematoxylin and eosin (H&E)–stained slides of 501 CRC patients, diagnosed between 2005 and 2010, were reevaluated for tumor budding according to the ITBCC criteria. Low (n = 331) was compared to intermediate/high budding (n = 170). The percentage of TILs was also assessed, and the following four groups were established: low budding + TILs >5% (n = 162), low budding + TILS ≤5% (n = 169), high budding + TILS >5% (n = 68), high budding + TILs ≤5% (n = 93). The combination of both markers revealed highly significant differences in overall survival (OS) between the four groups (P =.001). The low budding/>5% TILs group showed longest OS, followed by high budding/>5% TILs cases, followed by tumors with low budding/≤5% TILs. OS was worst for the high budding/≤ 5% TILs group. The combined score also correlated with T, N, M, L, Vstaging, development of disease relapse and distant metastasis. Our study shows that — even in the age of molecular pathology — it is still important to pay special attention to tumor morphology for additional information on tumor behavior and prognosis. Combining different morphological parameters of tumor and tumor environment can help to further subdivide CRC into new prognostic groups.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Budding; Colorectal cancer; Prognosis; Subgroups; Tumor- infiltrating lymphocytes (TILs)